2022
DOI: 10.1177/21582440221088013
|View full text |Cite
|
Sign up to set email alerts
|

Regional Tourism Performance Research: Knowledge Foundation, Discipline Structure, and Academic Frontier

Abstract: In order to promote the prosperity and development of the research on “regional tourism performance” and better guide the practice of regional tourism development, this paper gives a basic and comprehensive review of the research activities on “regional tourism performance.” Data were collected from 418 English papers (2004–2020) collected from the Web of Science database. This study uses CiteSpace and Gephi to analyze the development of the thematic research from four dimensions: research overview, knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Hair et al, 2010). Further, the AVE that varied from .711 to .867 (..50) for convergent validity, has also adequately met the test assumptions (J. F. Hair et al, 2013;Hashmi, Amirah, Yusof, & Zaliha, 2020).…”
Section: Confirmatory Factor Analysis (Cfa)mentioning
confidence: 79%
See 2 more Smart Citations
“…Hair et al, 2010). Further, the AVE that varied from .711 to .867 (..50) for convergent validity, has also adequately met the test assumptions (J. F. Hair et al, 2013;Hashmi, Amirah, Yusof, & Zaliha, 2020).…”
Section: Confirmatory Factor Analysis (Cfa)mentioning
confidence: 79%
“…While Achua (2011) found that public sector organizations are unwilling to adopt online systems due to a lack of competencies and knowledge that impedes organizational performance. Conversely, knowledge enhances the performance of a novice for a particular role or job (Guo & Zhang, 2022;Lamjahdi et al, 2020;Lueck & Peek, 2012;Steensma & Groeneveld, 2010). Naidoo and Wu (2011) researched 570 inventory control experts from New Zealand, Australia, the United States, and the United Kingdom and established that the designated staff could professionally plan and control the inventory effectively if knowledge had been imparted to them.…”
Section: Knowledge and Inventory Managementmentioning
confidence: 99%
See 1 more Smart Citation